ClpV recycles VipA/VipB tubules and prevents non‐productive tubule formation to ensure efficient type VI protein secretion. Issue 5 (3rd February 2013) - Kapitein, Nicole; Bönemann, Gabriele; Pietrosiuk, Aleksandra; Seyffer, Fabian; Hausser, Ingrid; Locker, Jacomine Krijnse; Mogk, Axel
Summary The multicomponent type VI secretion system (T6SS) mediates the transport of effector proteins by puncturing target membranes. T6SSs are suggested to form a contractile nanomachine, functioning similar to the cell‐puncturing device of tailed bacteriophages. The T6SS members VipA/VipB form tubular complexes and are predicted to function in analogy to viral tail sheath proteins by providing the energy for secretion via contraction. The ATPase ClpV disassembles VipA/VipB tubules in vitro, but the physiological relevance of tubule disintegration remained unclear. Here, we show that VipA/VipB tubules localize near‐perpendicular to the inner membrane of Vibrio cholerae cells and exhibit repetitive cycles of elongation, contraction and disassembly. VipA/VipB tubules are decorated by ClpV in vivo and become static in ΔclpV cells, indicating that ClpV is required for tubule removal. VipA/VipB tubules mislocalize in ΔclpV cells and exhibit a reduced frequency of tubule elongation, indicating that ClpV also suppresses the spontaneous formation of contracted, non‐productive VipA/VipB tubules. ClpV activity is restricted to the contracted state of VipA/VipB, allowing formation of functional elongated tubules at a T6SS assembly. Targeting of an unrelated ATPase to VipA/VipB is sufficient to replace ClpV function in vivo, suggesting that ClpV activity is autonomously regulated by VipA/VipB conformation.